فاعلية منهج تعليم اللغة العربية في برنامج (j-QAF)في المدارس الإبتدائية الحكومية بماليزيا :b - Asma' Ammar (Kulliyah Ma'arif al-Wahy wa al-'Ulum al-Insaniyah, al-Jami'ah al-Islamiyah al-'Alamiyah Maliziya, 2009)
This study aims at analyzing the efficiency of curriculum in the teaching of Arabic Language in (j-QAF) program at government primary schools in Malaysia. The efficiency of curriculum in the teaching of Arabic Language in (j-QAF) will be based on the elements of curriculum. The study is trying to recognize the substance and elements of Arabic Language curriculum for non-native speakers. Besides, it also describes and evaluates the usage of Arabic curriculum in (j-QAF). Hence, the study will be able to find positive and negative effects of the efficiency of curriculum used in (j-QAF). Furthermore, it will also reveal the problems and criticism regarding the curriculum. In addition, it also focuses on the learning outcomes of Arabic Language study among the learners. The study also will emphasize on the significance of Arabic curriculum in (j-QAF) and help teachers in choosing the best method of teaching to the beginners. At the end of the study, the researcher will circulate questionnaire and hold personal interview with teachers to find out some information related to the study.